2010
DOI: 10.1002/elps.200900451
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic studies of radiation‐induced apoptosis of human leukocytes by capillary electrophoresis‐mass spectrometry and flow cytometry: Adaptive cellular responses to ionizing radiation

Abstract: There is growing interest in the development of new methods for elucidating the biological effects of low-dose exposure to ionizing radiation (IR) on human health. Herein, we introduce a strategy for assessment of the impact of radiation-induced oxidative stress on the intra-cellular metabolism of human leukocytes. Untargeted metabolomic analyses were performed by CE-ESI-MS on irradiated leukocytes exposed to increasing doses of -radiation emitted from a Taylor source, which were subsequently incubated for 44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 64 publications
3
29
0
Order By: Relevance
“…1A). As expected, irradiation of WT Jurkat T cells resulted in profound alterations in cellular metabolism (4,7). Of the 342 named metabolites quantified, 27 were significantly altered at 2 h and 112 at 8 h after irradiation (Table 1).…”
Section: Cd47 Controls Global Metabolic Resistance To Radiation-supporting
confidence: 64%
See 1 more Smart Citation
“…1A). As expected, irradiation of WT Jurkat T cells resulted in profound alterations in cellular metabolism (4,7). Of the 342 named metabolites quantified, 27 were significantly altered at 2 h and 112 at 8 h after irradiation (Table 1).…”
Section: Cd47 Controls Global Metabolic Resistance To Radiation-supporting
confidence: 64%
“…CD47 Limits Oxidative Stress Responses-The glutathione and glyoxalase pathways are critical for cellular redox homeostasis, and previous metabolomics studies documented that these pathways are compromised by exposure of cells to IR (4,7). Levels of oxidized and reduced glutathione fell progressively as expected in irradiated WT cells (Fig.…”
Section: Volume 290 • Number 41 • October 9 2015mentioning
confidence: 71%
“…Untargeted metabolomic analyses were performed by CE-ESI-MS on irradiated leukocytes exposed to increasing doses of radiation emitted from a Taylor source, which were subsequently incubated for 44 h to allow for cellular recovery [48]. CE-ESI-MS analysis of filtered white blood cell lysates was performed to quantify changes associated with 22 intra-cellular metabolites, which were consistently measured in leukocytes across all radiation levels.…”
Section: Selected Methodsmentioning
confidence: 99%
“…Kok et al demonstrated that additions of triethylamine to the BGE and sheath liquid are favorable for the detection sensitivity of anionic metabolites in CE‐MS . Metabolomic studies of radiation‐induced apoptosis of human leukocytes by CE‐MS revealed a nonlinear upregulation of specific metabolites, arginine, glutamine, creatine, proline, and reduced glutathione as adaptive cellular responses to ionizing radiation .…”
Section: Analytical Applicationsmentioning
confidence: 99%